Novel approach to imaging active takayasu arteritis using somatostatin receptor positron emission tomography/magnetic resonance imaging. - Tarkin,JM; Wall,C; Gopalan,D; Aloj,L; Manavaki,R; Fryer,TD; Aboagye,EO; Bennett,MR; Peters,JE; Rudd,JHF; Mason,JC (Circulation: Cardiovascular Imaging, 2020)
Although 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET) is an important diagnostic test for Takayasu arteritis (TAK),118F-FDG lacks inflammatory cell selectivity and cannot accurately distinguish arteritis from metabolically active vascular remodeling.2 This observation has led to the search for more sensitive and specific PET tracers for TAK. Macrophage activation antigen SST2 (somatostatin receptor subtype-2) PET represents a potential alternative imaging biomarker for defining disease activity in TAK, as macrophages are a major feature of the inflammatory infiltrate. We aimed to determine the ability of SST2 PET/magnetic resonance imaging (MRI) to detect arteritis in 2 patients with clinically active TAK.